2013
DOI: 10.1016/j.psyneuen.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Influences of early shift work on the diurnal cortisol rhythm, mood and sleep: Within-subject variation in male airline pilots

Abstract: SummaryWe aimed to investigate how early and late work shifts influenced the diurnal cortisol rhythm using a within-subjects study design. Participants were 30 healthy male non-smoking pilots, mean age 39.4, employed by a short-haul airline. The standard rotating shift pattern consisted of 5 early shifts (starting before 0600 h), followed by 3 rest days, 5 late shifts (starting after 1200 h) and 4 rest days. Pilots sampled saliva and completed subjective mood ratings in a logbook 6 times over the day on two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 53 publications
1
27
1
Order By: Relevance
“…The circadian rhythm of cortisol means that the timing of the saliva collection is critical in order to make comparisons between days. Typically, saliva samples are collected based on either time of awakening [58][59][60][61] or time of day [62][63][64][65]. The samples in this study were collected "before going to sleep" and, as such, may have been at different times on different days, limiting the conclusions that can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian rhythm of cortisol means that the timing of the saliva collection is critical in order to make comparisons between days. Typically, saliva samples are collected based on either time of awakening [58][59][60][61] or time of day [62][63][64][65]. The samples in this study were collected "before going to sleep" and, as such, may have been at different times on different days, limiting the conclusions that can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent study, researchers experimentally manipulated the sleep schedules of a sample of young adults and found that depriving sleep resulted in higher morning cortisol levels, whereas sleep misalignment (i.e., wakefulness at times the SCN is promoting sleep and sleep at times when wakefulness is being reinforced by the SCN) resulted in lower morning cortisol levels (Wright et al, 2015). Other studies among shift workers, who routinely manipulate their sleep schedules, have shown that working later shift times is associated with a reduced CAR compared to individuals on regular sleep (e.g., Williams et al, 2005; Bostock and Steptoe, 2013). Less is known about associations between sleep variability and diurnal cortisol among individuals that experience normative fluctuations in their sleep schedules.…”
Section: Introductionmentioning
confidence: 97%
“…Glucocorticoids are the final mediators in HPA axis cascade and critical for the pathogenesis of sustained stress-related sleep disorders. Many researchers have reported that sustained stress 4 5 increases cortisol levels and can induce sleep disorders, including poor sleep quality and shorter sleep duration. Corticosteroid receptors, glucocorticoid receptors (GRs) and mineralocorticoid receptors (MRs), are highly expressed in the brain 6 .…”
mentioning
confidence: 99%